A king’s own son, named Mops (or Mucks?): about fantasy inscriptions, antique storytelling and name records between Pylos and Karatepe - Diether Schürr (Gephyra, 2019)
After the discovery of the long Phoenician and Hieroglyphic Luwian inscriptions of Karatepe (Cilicia), which mention a certain Muksas or MPŠ as the founder of a dynasty, this name was immediately linked with a fabled Greek seer named Mopsos, because some authors tell that he traveled, after the fall of Troy, to Pamphylia and also to Cilicia and even ruled there. These names were linked with other male names too: Mycenaean Mokwsos (?), Muksus in a Hittite text, the Lydian name (in Greek adaption) Moxos and, finally, Phrygian Muksos. The famous archaeologist James Mellaart even invented a long Bronze Age Hieroglyphic Luwian inscription, published recently, where a Great King’s son named Muksus came to the city of Ashkelon, as did the Lydian called Mopsos in the ‘Deipnosophists’ of Athenaeus.Without placing such confidence in storytelling, late and very late and not altogether trustworthy, it is easier to suppose that the Cilician MPŠ was identified with the Greek Mopsos only much later and to leave open why the founder of the dynasty had two similar but different names. And nothing speaks for a Bronze Age date for this founder – on the contrary, in the Hieroglyphic Luwian inscription from Çineköy near Adana the donating king is his grandchild, and this must probably be taken literally, not merely as ‘descendant’. The Mycenaean Mokwsos may indeed have been adapted in West Anatolia as Muksus, and this handed down in Lydia and then first taken over by Phrygians and later by Luwians from Phrygians: travels of a name and not travels of the fabled seer. It is however not cogent that the names attested in Anatolia are derived from Mycenaean; they could be easily independent.